Analiza Systemów Motywacji Pracowników Zaangażowanych w Działalność Innowacyjną - Popova, Irina Anatoliivna; Martynovych, Nataliia Oleksandrivna (Warszawa : Drukarnia «Victoria», 2014)
The article provides a thorough analysis of the motivation systems of employees involved in innovative activities in enterprises of various industries. The authors emphasize the need to take into account the personal needs and characteristics of employees when forming an effective motivation system. The study reveals the dominance of material incentives, such as bonuses and salary increases, but also draws attention to the importance of non-material incentives, social programs and professional development opportunities. The article offers methodological approaches to the analysis of motivations, points to the low level of innovative activity in a number of enterprises and justifies the need to create a strategically oriented motivation system that would contribute to the growth of staff creativity and ensure the sustainable development of the enterprise.

У статті здійснено ґрунтовний аналіз систем мотивації працівників, залучених до інноваційної діяльності в підприємствах різних галузей. Авторки наголошують на необхідності врахування особистісних потреб і особливостей працівників при формуванні ефективної мотиваційної системи. Дослідження виявляє домінування матеріальних стимулів, як-от премії та підвищення заробітної плати, але також звертає увагу на значення нематеріальних заохочень, соціальних програм і можливостей професійного розвитку. Стаття пропонує методичні підходи до аналізу мотивацій, вказує на низький рівень інноваційної активності в ряді підприємств і обґрунтовує потребу у створенні стратегічно орієнтованої системи мотивації, яка б сприяла зростанню креативності персоналу й забезпеченню сталого розвитку підприємства.
Analysis Of Motivation Systems Of Employees Engaged In Innovative Activities
Keywords: personnel motivation; innovative activity; incentive system; non-material incentives; innovative activity; personnel management; employee creativity; мотивація персоналу; інноваційна діяльність; система стимулювання; нематеріальні заохочення; інноваційна активність; управління персоналом; креативність працівників